2016
DOI: 10.1016/j.neuroscience.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Third trimester-equivalent ethanol exposure causes micro-hemorrhages in the rat brain

Abstract: Exposure to ethanol during fetal development produces long-lasting neurobehavioral deficits caused by functional alterations in neuronal circuits across multiple brain regions. Therapeutic interventions currently used to treat these deficits are only partially efficacious, which is a consequence of limited understanding of the mechanism of action of ethanol. Here, we describe a novel effect of ethanol in the developing brain. Specifically, we show that exposure of rats to ethanol in vapor chambers during the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The cell death is not necessarily and exclusively caused by impairments of the neurotransmitter system. Indirect effects, such as those related to the disruption of brain or uterine vasculature, may play a role in alcohol-induced cell death [ 14 , 15 , 16 ].…”
mentioning
confidence: 99%
“…The cell death is not necessarily and exclusively caused by impairments of the neurotransmitter system. Indirect effects, such as those related to the disruption of brain or uterine vasculature, may play a role in alcohol-induced cell death [ 14 , 15 , 16 ].…”
mentioning
confidence: 99%
“…A rat study, with a range of alcohol exposure doses, found resulting microhemorrhages in the brain that led to neuronal loss concentrated in the cortex, including the cingulate cortex. 29 Supporting this finding, structural MRIs show that alcohol-exposed individuals had reduced overall volume, grey matter, and white matter in the cingulate gyrus, one component of the cingulate cortex, as well as the CC. Despite controlling for overall change in volume, white matter presented significantly reduced compared with controls.…”
Section: Introductionmentioning
confidence: 75%
“…Ethanol vapor or gavage exposure of early postnatal (P3-5) rats resulted in brain micro-hemorrhages, which occurred at both low and high ethanol concentrations. These micro-hemorrhages occurred principally in the cerebral cortex, but were also observed in other brain regions (Welch et al, 2016).…”
Section: Postnatal Models Of Fasdmentioning
confidence: 81%